In silico toxicity of the natural pesticides clitoriacetal and 6-deoxyclitoriacetal: an ecotoxicological strategy - Sousa, Damião Sampaio de; Belarmino, Anthony Barbosa; Oliveira, Victor Moreira de; Mendes, Francisco Rogênio da Silva; Marinho, Emmanuel Silva; Marinho, Gabrielle Silva (Revista de Ciências Agroveterinárias, 2023)
Brazil has a position of visibility in the popularization of pesticides which has caused public and environmental health problems. Thus, the search for new natural insecticides that meet appropriate guidelines is found in plants, as is the case of the compounds clitoriacetal and 6-deoxyclitoriacetal isolated from plants of the genus Clitoria constituted of rotenoids with insecticidal activity. In this context, this study aims to investigate the in silico toxicity of the pesticides clitoriacetal and 6-deoxychlitoriacetal in A. melifera bees, enabling the biosafety of these organisms. Based on the in silico models: BeetoxAl© (acute oral toxicity) and molecular docking a criteria for biochemical evaluation. In this way, it was established that the derivatives clitoriacetal and 6-deoxycyclitoriacetal have oral toxicological potential (acute) due to the various hydrogen acceptor sites and low quantitative exposure value. And from the molecular docking, it is pointed out that the complexes formed between the ligands and protein of A. melifera present similar three-dimensional positions but do not express any interaction with amino acids of the binding site of A. melifera conferring them low toxicity. The study was developed in an initial character, that is, it will still be necessary to improve and deepen the techniques applied and expand new in silico and in vivo assays.